Civil protection of the right to the integrity of the fetus’s body (comparative study) - Ako Fatih Hama Rash; Dilawar Saleh Mahmoud (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
The fetus is considered grains of the family, so most systems tendto protected it, ending a pregnancy is a crime and the perpetrator is punished, even if the crime was committed by his closest relatives, or even the mother. The civil law gives civil protection to the right of integrity of the body, which is one of the rights inherent in his personality, and the legal personality of a person starts from the time of his birth alive, and the unborn fetus must be recognized as a discretionary figure for its comparison to its discretionary life to give civil protection to the rights granted. Accordingly, we divided the topic of the research in two arenas. In the first arena, we explained the right to the integrity of the fetus’s body through detailing the right to the integrity of the body in general and recognition of the same fetus, because the Iraqi Civil Code has given civil protection to (the soul) in Article (202) furthermore, it discussed in the second arena the civil protection of the fetus by proving the ability of the fetus, protection his or her right in financial transactions, and thus his right to the integrity of his body, and we concluded the research with the most important results that we reached and useful recommendations.